Implementasi Metode Linear Congruential Generator (LCG) Dalam Game Puzzle Fosil Berbasis Hand Tracking (Studi Kasus: Museum Purba Unit Bukuran) - Hidayat, Fahrul; Setiyowati, Setiyowati; Budiadi, Hasman; Kusumaningrum, Andriani (Jurnal Ilmiah SINUS, 2025)
In the digital era, the use of interactive technology is increasingly widespread, including in the fields of education and entertainment. This study aims to develop a fossil Puzzle Game based on Hand Tracking at the Museum Purba Unit Bukuran using the Linear Congruential Generator (LCG) method to generate varied and random challenges. The implementation of LCG in this Game is expected to enhance the variation and randomization of Puzzle pieces, providing a more engaging and immersive learning experience for visitors. The Hand Tracking method is chosen to offer a more natural and intuitive interaction, allowing users to interact with the Game using hand gestures without the need for additional devices such as a mouse or keyboard. This technology not only increases user comfort but also adds an interactive element that brings the virtual experience closer to reality. The results of the study show that the use of LCG successfully randomizes Puzzle pieces with great variation, thus increasing the Game's replayability. Additionally, the integration of Hand Tracking in the Game enhances user engagement and satisfaction. Trials conducted on a group of museum visitors showed positive responses, with the majority of participants finding the Game enjoyable and interactive.